Perancangan Ulang Interior Rumah Tinggal Solo Baru dengan pendekatan Smart & Eco Design (Studi Kasus Luasan 100, 150 & 240) - Henry Christian Tjandra; I Gusti Ngurah Ardana; Sherly De Yong (Intra, 2017)
Interior sector within existing house at Solo Baru Area has been highly affecting the environment damage due to highly energy consumed. This fact was caused due to a large amount of construction and existing building on specified area doesn’t have any environmental preservation aspect approach. As an interior designer, it will be a proper responsibility to apply the micro scale energy efficient solution to the construction sector. Smart and eco design is a solution to the highly produced emission in the global issue.This design use design thinking as its method, by collecting data, ideate the concept, and to aplly the idea. The application of Eco design is by optimalize the using of natural energy by maximize the room circulation, low emission materials and low energy furnitures. They are applied to preserve the environment system. While Smart Interior is a design concept to optimize the interior by using technology that will give efficiency and newly experience purpose to the living human inside. This design, based on smart and sustainable concept, resulting a recycling method and an effective technique in finishing to save time and lowering the emission. Smart concept which is applied in this interior design is an integrated control panel and also technology for energy and water saving, in example, solar panel and waste water cycling.